The use of a front-end ZVZCS DC-DC converter for an IoT VFD inverter system in the paddle wheel machine drive applications - Chirdchoo, Nitthita; Meesrisuk, Watanyu; Chuenta, Weerasak (Institute of Advanced Engineering and Science, 2024)
This research paper proposes the integration of power electronics and internet of things (IoT) technologies to apply in shrimp farms. By focusing on the design of a front-end converter, a three-level half-bridge (3L-HB) DC-DC converter with the zero voltage and zero current switching (ZVZCS) technique is chosen to be the front-end power converter to supply the DC bus voltage for the variable frequency drive (VFD) inverter for the paddle wheel machine in the shrimp pond. To confirm the effectiveness and possibility of the proposed concept, the circuit was theoretically designed and tested at 540 V DC of the input voltage, 700 V DC of the DC bus voltage and 3 kW of rated power. It is found that, the front-end converter can step up the DC bus to be 700 V DC which is enough for operating the VFD inverter. All switches can achieve the soft switching condition ZVZCS resulting in decreasing the switching loss and increasing the reliability of the circuit. The maximum experimental efficiency of the front-end converter is 94.9% at 75% of a full load. In addition, the introductory concept of using the IoT system also presents to improve the shrimp farming method.